The narwhal (Monodon monoceros) cementum–dentin junction: A functionally graded biointerphase. (August 2014) - Grandfield, Kathryn; Chattah, Netta Lev-Tov; Djomehri, Sabra; Eidelmann, Naomi; Eichmiller, Frederick C; Webb, Samuel; Schuck, P James; Nweeia, Martin; Ho, Sunita P
In nature, an interface between dissimilar tissues is often bridged by a graded zone, and provides functional properties at a whole organ level. A perfect example is a "biological interphase" between stratified cementum and dentin of a narwhal tooth. This study highlights the graded structural, mechanical, and chemical natural characteristics of a biological interphase known as the cementum–dentin junction layer and their effect in resisting mechanical loads. From a structural perspective, light and electron microscopy techniques illustrated the layer as a wide 1000–2000 μm graded zone consisting of higher density continuous collagen fiber bundles from the surface of cementum to dentin, that parallels hygroscopic 50–100 μm wide collagenous region in human teeth. The role of collagen fibers was evident under compression testing during which the layer deformed more compared to cementum and dentin. This behavior is reflected through site-specific nanoindentation indicating a lower elastic modulus of 2.2 ± 0.5 GPa for collagen fiber bundle compared to 3 ± 0.4 GPa for mineralized regions in the layer. Similarly, microindentation technique illustrated lower hardness values of 0.36 ± 0.05 GPa, 0.33 ± 0.03 GPa, and 0.3 ± 0.07 GPa for cementum, dentin, and cementum–dentin layer, respectively. Biochemical analyses including Raman spectroscopy and synchrotron-source microprobe X-ray fluorescence demonstrated a graded composition across the interface, including a decrease in mineral-to-matrix and phosphate-to-carbonate ratios, as well as the presence of tidemark-like bands with Zn. Understanding the structure–function relationships of wider tissue interfaces can provide insights into natural tissue and organ function.